Adjuvant use of combination of antibiotics in acute severe ulcerative colitis: A placebo controlled randomized trial. Issue 7 (3rd July 2021) - Mishra, Shubhra; Mandavdhare, Harshal S; Singh, Harjeet; Choudhury, Arup; Shah, Jimil; Ram, Sant; Kalsi, Dimple; Samanta, Jayanta; Prasad, Kaushal K; Sharma, Arun K; Dutta, Usha; Sharma, Vishal
ABSTRACT: Objectives: Evaluation of a combination of antibiotics as an adjuvant therapy in acute severe ulcerative colitis (ASUC). Methods: Patients with ASUC were randomized to either infusions of placebo or intravenous ceftriaxone and metronidazole in addition to standard care. Primary outcome was response on day three according to Oxford's criteria. Secondary outcome measures included changes in partial Mayo score, CRP levels, fecal calprotectin (day three), and need for second-line therapy, hospital stay, and mortality (day 28). Results: Fifty patients (25 in each group, median age: 33 years, 23 males) were included. The number of patients with fulminant disease in the antibiotic group were 16 (64%) as compared to 7 (28%) in the standard of care group. Complete response on day three was attained by 7 (28%) in the antibiotic and 6 (24%) standard of care group (p = 1.00). Three patients from the antibiotic group underwent colectomy and three received intravenous cyclosporine whereas four patients in the standard of care group received cyclosporine (p = 0.725). There was no significant difference in change in CRP, Partial Mayo score, and fecal calprotectin between the two groups on day three. Conclusion: Combination of intravenous ceftriaxone and metronidazole did not improve outcomes in ASUC. Acronym: AAASUC trial Registration Number: CTRI/2019/03/018196 and NCT03794765